The later Saxon and early Norman manorial settlement at Guiting Power, Gloucestershire : archaeological investigation of a Domesday book entry - Marshall, Alistair (Archaeopress Archaeology, 2020)
This volume outlines an investigation of the early manor at Guiting Power, a village in the Cotswolds with Saxon origins, lying in an area with interesting entries in the Domesday Survey of 1086.